Effects of Ficus umbellata (Moraceae) Aqueous Extract and 7-Methoxycoumarin on Scopolamine-Induced Spatial Memory Impairment in Ovariectomized Wistar Rats - Stéphane Zingue; Harquin Simplice Foyet; Sefirin Djiogue; Yannick Ezo’o Ezo’o; Hervé Hervé Ngatanko Abaïssou; Pafroumi Fachagbo; Dieudonné Njamen (Behavioural Neurology)
The present work was undertaken to evaluate the ability of F. umbellata aqueous extract and its major component 7-methoxycoumarin (MC) to improve scopolamine-induced spatial memory impairment in ovariectomized Wistar rats. For this to be done, 10 sham-operated and 30 postmenopausal-like rats were randomly distributed in eight groups (n=5) and treated with distilled water (2 mL/250 g), estradiol valerate (1 mg/kg BW), piracetam (1.5 mg/kg BW), F. umbellata aqueous extract (50 and 200 mg/kg BW), or MC (1 mg/kg BW) for 21 consecutive days. Before and after the memory impairment with scopolamine (2 mg/kg BW), animals underwent behavioral evaluations on Y- and radial mazes. As results, age and ovariectomy did not induce significant changes in the reference memory errors. While age decreased working memory errors, ovariectomy increased it. The MC as well as F. umbellata extract significantly increased (p<0.01) the percentage of spontaneous alternation and decreased (p<0.001) working and spatial reference memory errors and anxiety parameters (rearing and grooming) in ovariectomized rats. MC significantly reduced (p<0.05) the MDA level, but resulted in an increase in GSH level in brain homogenates. These results suggest that MC is endowed with neuroprotective effects and could account for the neuroprotective effects of F. umbellata in rats.